ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Siti Wulandari, 14.05.52.0100; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2018)
The purpose of this study is to analyze the effect of profitability, leverage, firm size, institutional ownership and managerial ownership of earnings management at manufacturing companies listed on the Indonesia Stock Exchange. This research uses purposive sampling method in sample selection, with sample criterion is a manufacturing company listed in Bursa Efek Indonesia (BEI) during period 2013-2016. Based on these criteria, obtained a sample of 120 companies during the four-year observation period. The relationship and / or influence between variables are explained by using logistic regression analysis method. The results showed that profitability had negative and insignificant effect, leverage had negative and insignificant effect, managerial ownership had negative and insignificant effect, firm size had positive and significant effect, and institutional ownership had negative and significant effect to earnings management. Keywords: Earnings Management, Profitability, Leverage, Company Size, Institutional Ownership and Managerial Ownership.